(untitled) (AYUSHDHARA, 2018)
Sandhigat vata is one of the most common degenerative articular disorder of the geriatric age group. It is a type of Vatavyadhi which mainly occurs in Vriddhavastha due to Dhatukshaya limiting routine activities. Lifestyle, excessive weight, trauma and calcium deficient diet, age factor are some of the causative factors. Trauma or joint injuries are becoming more common reason of OA in younger adults. It being a Vatavyadhi, located in Marmasthisandhi and its occurrence in old age group makes it Kasthasadhya. Vata dosha, is mainly affected in this disease which creates Sandhishool, Sandhishoth, Vatapoornadruti sparsha, lack of movements of joints or painful movements of joints i.e., Prasaran aakunchan pravrutti savedana. The present case report is a case of Aagantuj/Kshataj sandhivata i.e. post traumatic osteoarthritis (PTOA). The assessment of efficacy of treatment was done by Knee Injury and Osteoarthritis Outcome Score (KOOS). Total two assessments were done, before treatment and after 3 months of treatment. After competition of the treatment, significant improvement was seen in pain, swelling, range of movement, walking distance and knee related quality of life of patient. The patient was successfully managed with Ayuevedic line of treatment. It can be concluded that PTOA cases can also be managed successfully with Ayurvedic intervention.